Monika Djerf-Pierre & Mats Ekström, A history of Swedish Broadcasting - Communicative ethos, genres and institutional change (Göteborg: Nordicom, 2013) - Birgir Guðmundsson (The University of Akureyri, 2015)
Book review for NOME by Birgir Guðmundsson, University of Akureyri: